Towards the development of a starter culture for improvement of grain storage through biopreservation - Larsson, Malin (2009)
In temperate countries such as Sweden, where much rain falls during the harvest period, problems can occur later during preservation of feed grains because of too high water contents in the grains. Drying by heated air is the most commonly used operation in Sweden to reduce water content in grains. If airtight storage is used instead, energy and money can be saved, as airtight storage only consumes 2 % of energy needed for heated air drying.